The Seren Taun Experience: A Catalyst for Sustainable Cultural Tourism and Visitor Loyalty in West Java - Riski Taufik Hidayah; Simerjeet Singh Bawa; Gusni Gusni; Eristy Minda Utami (Media Ekonomi dan Manajemen, 2025)
This study examines the impact of engaging in the Seren Taun ritual at the Ciletuh-Palabuhanratu UNESCO Global Geopark (CPUGGp) on tourist loyalty, with an emphasis on Memorable Tourism Experiences (MTEs) within three indigenous communities: Ciptagelar, Sinaresmi, and Ciptamulya. This study investigates how MTEs influence tourist loyalty by exploring destination image, visitor engagement, and cultural interaction. A quantitative method was utilized involving 200 participants who attended Seren Taun, with data collected through Google Forms. The application of Structural Equation Modeling (SEM) through the PLS technique, utilizing SmartPLS 4.0, facilitated the assessment of reliability, validity, and correlation analysis. The results demonstrate that MTEs play a crucial role in improving destination image and fostering cultural interaction, yet they do not markedly boost visitor engagement. The influence of MTEs on loyalty intention is significant, underscoring the importance of enhancing destination image and cultural engagement to promote the growth of cultural tourism in Geoparks. The research highlights the significance of cultural interaction and MTEs in fostering tourist loyalty. Rituals such as Seren Taun enhance visitors' ties to the local culture and encourage sustainable tourism, positively impacting local economies.